Zakat and Social Welfare: Reviewing Zakat Management in Baitul Mal Aceh through a Good Governance Perspective - Dahlawi Dahlawi; Ilham Akbar; Saddam Rassanjani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Zakat has the excellent potential to overcome social welfare problems. Baitul Mal Aceh (BMA) is a body that can maximize the benefits of zakat funds for the welfare of the poor in Aceh province; therefore, it is necessary to strive for better management of zakat to obtain better results. This study aims to determine the management of zakat in BMA in terms of a good governance approach. The method used in this study is a qualitative descriptive method with data obtained through interviews, observation, and document study. The research results show that the zakat management in Aceh is quite good. Management should be based on the principles of good governance, such as openness and transparency; societal participation; accountability; and effectiveness and efficiency. Hopefully, BMA can continue to maintain and even improve its performance in managing zakat, so that it can improve the welfare of zakat recipients in Aceh.